(untitled) (Eurasian Medical Research Periodical, 2026)
Breast cancer represents one of the most prevalent malignancies worldwide, with bone metastasis occurring in approximately 65–75% of patients with advanced-stage disease. The colonisation of the skeletal system by tumour cells precipitates a debilitating cycle of osteolytic and osteoblastic destruction, significantly compromising patient survival, functional capacity, and quality of life. This review critically analyses and compares the therapeutic landscape governing breast cancer–related bone metastasis, from established modalities—including chemotherapy, endocrine therapy, and external beam radiotherapy—to contemporary advances in targeted therapy, bone-modifying agents, immunotherapy, and precision medicine.